2014
DOI: 10.1161/strokeaha.113.003071
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Prehospital Stroke Scale to Predict Large Arterial Occlusion

Abstract: The RACE scale is a simple tool that can accurately assess stroke severity and identify patients with acute stroke with large artery occlusion at prehospital setting by medical emergency technicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
346
0
30

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 401 publications
(391 citation statements)
references
References 29 publications
6
346
0
30
Order By: Relevance
“…The presented test has a higher sensitivity and NPV than other tests (Table 4) (Hastrup et al., 2016; Katz et al., 2015; Lima et al., 2016; McMullan et al., 2017; Nazliel et al., 2008; Pérez de la Ossa et al., 2014; Scheitz et al., 2017; Singer et al., 2005). We found that the FAST PLUS test had a high sensitivity of 93% and high NPV of 94%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presented test has a higher sensitivity and NPV than other tests (Table 4) (Hastrup et al., 2016; Katz et al., 2015; Lima et al., 2016; McMullan et al., 2017; Nazliel et al., 2008; Pérez de la Ossa et al., 2014; Scheitz et al., 2017; Singer et al., 2005). We found that the FAST PLUS test had a high sensitivity of 93% and high NPV of 94%.…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled 435 patients with median NIHSS scores of 8 into our study. The number of patients and NIHSS scores is comparable to the RACE study (Pérez de la Ossa et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations